MEDIATING EFFECT OF BRAND IMAGE AND BRAND TRUST BETWEEN E-WOM ON SMARTPHONE BUY INTEREST IN TANGERANG CITY - Dewi F.M. (Russian Journal of Agricultural and Socio-Economic Sciences, 2021)
The population in this study is the people in Tangerang City who are at least 17 years old and know about smartphone products. The sample was taken by 150 respondents using purposive sampling. The data were obtained through questionnaires on the Likert scale 1-5, which has been widely used as an interval scale. The data was analyzed using Partial Least Square with the Smart PLS-3 software application program. From the results of this study can be concluded that: First, there is a positive and significant influence between eWOM on Brand Image with a value of 30,399 > 1.96 Second, there is a positive and significant influence between eWOM on Buy Interest with a value of 2,788 > 1.96. Third, there is a positive and significant influence between eWOM on Brand Trust with a value of 10,238 > 1.96. Fourth, there is a positive and significant influence between Brand Image on Buy Interest with a value of 4,896 > 1.96. Fifth, there is a positive and significant influence between Brand Trust on Buy Interest with a value of 2,774 > 1.96. Sixth, there is a positive and significant influence between eWOM on Buy Interest through Brand Image with a Sobel test statistic of 4,718 > 1.96. Seventh, there is a positive and significant influence between eWOM on Buy Interest through Brand Trust with a Sobel test statistic of 2,247 > 1.96.